RESEARCH ON THE IMPACT OF DIGITAL TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE ON THE QUALITY AND ACCESSIBILITY OF EDUCATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In recent years, education has undergone significant transformations under the influence of digital transformation. The rapid development of digital technologies became especially evident after the COVID-19 pandemic, when millions of students and teachers were forced to transition to distance learning formats. This shift became a powerful catalyst for the implementation of new solutions, ranging from online platforms and mobile applications to intelligent learning systems and the automation of educational processes.Modern education can no longer be imagined without components such as cloud storage, learning management systems (LMS), adaptive learning technologies, and AI-based tools. These technologies are changing the very nature of interaction between teacher and student, making the learning process more flexible, accessible, and personalized. There is a growing need to analyze the effectiveness of their use, identifying both advantages and potential risks.